CGIAR Climate Insights, Issue 6, 16 April 2024 - Marshall, Suzie; Mukherji, Aditi (CGIAR Climate Change Impact Platform, 2024)
Welcome to Issue #6 of Climate Insights, the Climate Impact Platform’s fortnightly roundup of the latest publications on climate change impacts and adaptation, mitigation measures, and the physical science from the literature. We’re tracking trending topics in the climate space and linking them to our work for a food secure future with a brief comment on the implications of this new research on our own portfolio of climate research for development. Also, stay tuned — we’re working hard on improvements in the way we bring you this news.